Analisis Kebutuhan Pengembangan LKPD Berbasis Model Problem Based Learning Di SMP Negeri 6 Siak Hulu - Mega Khairani Ulfa; Yeyendra; Nurkhairo Hidayati (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
This study aims to analyze the need for developing Student Worksheets (Lembar Kerja Peserta Didik / LKPD) based on the Problem Based Learning (PBL) model at SMP Negeri 6 Siak Hulu. Needs analysis was conducted as the initial stage of development research to determine the suitability of teaching materials with the demands of the Merdeka Curriculum and the characteristics of students. The research employed a Research and Development (R&D) method using the 4D model, limited to the define stage (needs analysis). The research subjects consisted of science teachers and 30 students of SMP Negeri 6 Siak Hulu. Data were collected using interview guidelines and Likert-scale questionnaires covering curriculum alignment, current teaching materials, the need for PBL-based LKPD, teaching methods, students’ critical thinking and problem-solving skills, and learning achievement. The data were analyzed using descriptive quantitative analysis with percentage calculations. The results indicate that both teachers and students require PBL-based LKPD as supporting teaching materials, as the existing materials have not fully facilitated active student engagement and the development of critical thinking skills. Therefore, the development of PBL-based LKPD is considered highly necessary to support meaningful and problem-oriented science learning.